Quality of life as outcome in the treatment of osteoporosis: the development of a questionnaire for quality of life by the European Foundation for Osteoporosis. - Lips, P; Cooper, C; Agnusdei, D; Caulin, F; Egger, P; Johnell, O; Kanis, J; Liberman, U; Minne, H; Reeve, J; Reginster, J; Vernejoul, d; et al. (1997)
The morbidity of osteoporosis is caused by fractures. Vertebral fractures lead to pain and disability and a decrease in quality of life. A Working Party of the European Foundation for Osteoporosis has developed a specific questionnaire for patients with established vertebral osteoporosis. This questionnaire is intended for use in clinical trials. The questionnaire consists of questions and visual analogue scales in the following domains: pain, activities of daily living, jobs around the house, mobility, leisure and social activities, general health perception and mood. The questionnaire has been translated from English into French, German, Italian, Hebrew, Swedish and Dutch. The questionnaire is currently being validated in a multicentre study involving patients with stable osteoporosis and control subjects. Preliminary results indicate that the reproducibility is sufficient and that the questionnaire is able to discriminate between patients with vertebral osteoporosis and control subjects.